Community Innovations Fund (CIF) as support systems for Climate Smart Villages (CSV) development and scaling - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Tested at CSV level in MyLoi and Guinayangan. The knowledge and experiences captured in research outputs will be translated into extension materials for promotion to local governments and NGO partners.